Filtering strategic coupling: territorial intermediaries in oil and gas global production networks in Southeast Asia. (10th December 2018) - Breul, Moritz; Revilla Diez, Javier; Sambodo, Maxensius Tri
Abstract: The Global Production Network (GPN) approach has not yet considered the importance of territorial intermediaries for strategic coupling. This article demonstrates how the prospects of strategic coupling for the case of Vietnam and Indonesia with the oil and gas GPN are affected by the gateway role of Singapore. Based on interviews, the analysis reveals how Singapore influences regional economic development along the GPN through different filtering mechanisms, limiting the potential for strategic coupling for Vietnam and Indonesia. For GPN research, the identified filtering mechanisms illustrate how the territoriality of GPNs contributes to differentiated territorial outcomes. The findings therefore indicate the need to intensify the appreciation of the particular territorial configuration of GPNs as this yields considerable explanatory power for understanding the unequal contours of the global economy.